PROJECT OF ORGANIZATION OF “ECOSYSTEM SERVICES” SPACE, “ECO-SCHOOL" CENTERS - Ismoilov Jaloliddin (Journal of new century innovations, 2022)
Annotation: in this article, thoughts on the project of organizing ecosystem services, accommodation, eco-school centers and its implementation are discussed.